Fundamentalisme Dan Radikalisme: Bentuk Penyimpangan Dari Cita Ideal Hukum Islam - St Halimang - St Halimang (Institut Agama Islam Negeri Metro, 2020)
The focus of this article is the existence of fundamentalism and radicalism in terms of the discourse construction of Islamic law. This discourse appears based on the possibility of deviating from the ideal ideals contained in the Qur'an and Hadith. This article tries to parse the patterns and characteristics of fundamentalism and radicalism whose axis is based on a religious understanding framework. Based on the search, it was found that, from the existing discourse, it was identified the potential and possibility of this understanding and movement, to emerge in the community. This indicates that there are people who are tough in expressing opinions related to religion, and some have even committed anarchist acts. So it can be concluded that the followers of fundamentalism and radicalism are very strict in conveying their ideas. In fact, they do not hesitate to commit acts of violence in the form of anarchism. However, even so they still have to be recognized as part of the components of society. Because basically, radicalism and fundamentalism movements are a form of attitude against the West and modernism which are considered to have given birth to westernism, secularism, hedonism, pragmatism, uncertainty and the emptiness of life